Uveal effusion syndrome (clinical case) - Yu. A. Belyy; A. V. Tereshhenko; M. A. Plahotnij (Oftalʹmologiâ, 2015)
The purpose — to evaluate the effectiveness of the posterior sclerectomy with the corneal trepan in a uveal effusion syndrome.Patients and methods. Patient 1. The man, 61 years, complained about a blindness of the right eye and the progressing decrease in vision of the left eye. According to data of examinations the diagnosis was: uveal effusion syndrome, detachment of the choroid, exudative retinal detachment, the complicated cataract of both eyes. Patient 2. The man, 62 years, with complaints to low vision of the right eye and a blindness of the left-hand eye. Diagnosis: uveal effusion syndrome, detachment of the choroid, exudative retinal detachment, the initial complicated cataract of the right eye. Subatrophy operated retinal detachment, complicated cataract, silicone into the vitreal cavity of the left eye. Both patients underwent trepanation posterior sclera. Results. The patient 1noted significant improvement of vision in both eyes at the last examination. Мisual acuity with correction was OD — 0,2, OS — 0.3. Intraocular pressure was normal, improvement of electrical sensitivity and lability was diagnosed. On ultrasound examination of the retina belonged, moderate swelling of the choroid remained. Patient 2. Visual acuity was 0,1 + 3,0 D at the time of the last inspection. According to the ultrasonic B-scan of the right eye retinal detachment decreased to 3,8 mm, moderate swelling of the choroid remained. The OСT has showed detachment of the neuroepithelium in the macula to 60 μm. In ultrasonic biomicroscopy circular, ciliochoroidal detachment to 0,15 mm was diagnised.Conclusion. Described clinical cases confirmed the almost complete recovery of patients with the uveal effusion syndrome. Sclerectomy with the use of corneal trepan is a technically simple procedure and helps to define the path of the outflow suprachoroidal fluid subtenon space.